(untitled) (Journal of Public Health Indonesian, 2025)
The nutritional status of pregnant women significantly influences stunting in toddlers, as reflected by upper arm circumference measurements during the first trimester. Based on the Indonesian Nutritional Status Survey, stunting in Batanghari Regency decreased to 24% in 2021 but rose again to 26% in 2022, highlighting pregnancy as a critical period affecting future life quality. This quantitative study employed an analytical observational method with a cross-sectional design, conducted in the Community Health Center Work Area in Batanghari Regency, focusing on areas with the highest stunting prevalence. The research was carried out over eight months (March–November 2023) with a sample of 245 pregnant women in their second and third trimesters. Results showed that 40.4% of pregnant women experienced anemia. Statistically significant factors influencing anemia among pregnant women included family income, upper arm circumference, body mass index, TT injection services, blood pressure monitoring, provision of iron supplement tablets, and uterine fundal height measurements. It is recommended to enhance pregnant women’s access to healthcare services to improve their awareness of anemia risks and support better nutritional and health outcomes, which in turn can reduce anemia prevalence.